Pengembangan Website Online Berbasis Blended Learning Untuk Meningkatkan Penguasaan Konsep Mata Pelajaran IPA - Nukhbatul Bidayati Haka; Siti Makrupah; Bambang Sri Anggoro (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2020)
Learning support facilities in AL-Azhar 3 Junior High School in Bandar Lampung are sufficient for the learning process of students, but not yet optimally in utilizing technology for the learning process. This study aims to determine the development and feasibility of online media websites based on blended learning to improve the mastery of the concepts of Natural Sciences in Biology in the online form. This type of Research and Development (RD). The feasibility of the product can be seen from the results of the percentage of validators with the criteria "very feasible". The percentage of validation of media experts was 83.33%, validation of material experts was 97.91%, validation of linguists was 95.83%, and students as respondents were 83.02% which showed the criteria of "very good". The effectiveness of using the independent T test results in the significance of 0.000 α α 0.05 so that Ho is rejected, which means there is a difference between the application of online website media based on blended learning with conventional media. The average value of N-Gain classes using online media websites based on blended learning obtained 0.67 results compared to power point media that is 0.43. Fasilitas pendukung pembelajaran di SMP AL-Azhar 3 Bandar Lampung cukup untuk proses kegiatan belajar mengajar tetapi, belum sepenuhnya berjalan pemanfaatan teknologinya. Tujuan penelitian ini untuk mengetahui pengembangan media website online berbasis blended learning untuk meningkatkan penguasaan konsep IPA Biologi dalam bentuk online. Penelitian ini berjenis Research and Development. Akumulasi hasil validator mengatakan produk ini “sangat layak”. Validator ahli media 83,33%, validator ahli materi 97,91%, validator ahli bahasa 95,83%, serta respon peserta didik 83,02% dengan kriteria “sangat baik”. Keefektivitasan di uji T independent memperoleh signifikasi 0,000 ˂ α 0,05 sehingga Ho ditolak, berarti ada divergensi antara penerapan media website online dan media powerpoint. Nilai rerata N-Gain kelas eksperimen lebih tinggi 0,67 dibandingkan kelas kontrol 0,43.Kata kunci: biologi, blended learning, penguasaan konsep, website online